2004
DOI: 10.1007/s00125-004-1593-2
|View full text |Cite
|
Sign up to set email alerts
|

Joint role of non-HDL cholesterol and glycated haemoglobin in predicting future coronary heart disease events among women with type 2 diabetes

Abstract: Aims/hypothesis. Non-HDL cholesterol (the sum of LDL, VLDL and IDL cholesterol) is considered to be particularly valuable in the management of dyslipidaemia in type 2 diabetes. However, it remains uncertain whether the association between non-HDL cholesterol and cardiovascular risk in type 2 diabetes depends on the status of hyperglycaemia. We aimed to determine whether non-HDL cholesterol predicts CHD events among diabetic women independently of currently established risk factors and the status of glycaemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
5
31
1
1
Order By: Relevance
“…Another study on female type 2 diabetic patients has revealed that association between non-HDL cholesterol and CHD risk is apparent in patients with elevated TG [43]. Moreover, significantly high serum TG levels have been found in diabetic patients with CHD as compared to non-diabetic patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…Another study on female type 2 diabetic patients has revealed that association between non-HDL cholesterol and CHD risk is apparent in patients with elevated TG [43]. Moreover, significantly high serum TG levels have been found in diabetic patients with CHD as compared to non-diabetic patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…The Strong Heart Study, which addressed only American Indians, showed that non-HDL-cholesterol is a better predictor of cardiovascular morbidity than LDL-cholesterol [17]. Two further studies of people with diabetes in the USA, who were free of cardiovascular disease at baseline, comprised 921 female nurses aged <65 years [18] and 746 male health professionals aged 46-81 years [19]. In both studies, non-HDL-cholesterol was considered a better predictor of cardiovascular disease than ApoB.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, a substantial number of reports have indicated that ApoB and non-HDL-cholesterol are better predictors than LDL-cholesterol in people with diabetes [16][17][18][19]. Few studies have been conducted, however, to compare non-HDL-cholesterol with ApoB [18,19]; the studies that have been reported were restricted to North America, and the results were mixed. It would be misleading to generalise the findings to other populations, for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, diabetes is the sixth highest cause of death by disease and the fastest growing chronic illness (Chittleborough et al, 2007). Diabetic patients are twice as likely to have high blood pressure, cholesterol disturbances and heart disease (Schulze et al, 2004). In 2013, it was estimated that one in four Australian adults has either diabetes or pre-diabetes, with one person being diagnosed every 5 min (Schmid et al, 2003).…”
Section: Introductionmentioning
confidence: 99%